Pharmacodynamics of vicadrostat for aldosterone synthase inhibition in patients with CKD - Gashaw, Isabella; Tuttle, Katherine R; Monroy Kuhn, Manuel; Pleiner, Sina; Delic, Denis; Cronin, Lisa; Shah, Shimoli V; Rossing, Peter (European journal of endocrinology, 2026)
Aldosterone synthase inhibition may affect cortisol synthesis due to homology between CYP11B2 (aldosterone synthase) and CYP11B1. The selectivity of vicadrostat, a highly selective aldosterone synthase inhibitor, for aldosterone suppression was evaluated by corticosteroid assessment in participants with albuminuric CKD (with or without T2D) in a randomized, double-blind, placebo-controlled phase 2 trial (NCT05182840)After randomization to receive empagliflozin 10 mg once-daily or matched placebo for an 8-week run-in (plus renin-angiotensin system inhibitors), 586 participants were re-randomized to receive vicadrostat (3, 10, or 20 mg once-daily) or matched placebo for 14 weeks, with a 4-week follow-up. Our analysis included 410 participants who completed treatment. Plasma corticosteroids (aldosterone, cortisol, corticosterone, 11-deoxycorticosterone, and 11-deoxycortisol) were measured using liquid chromatography tandem mass spectrometry. Effects were evaluated via mixed effects models for repeated measures.Dose-dependent suppression of plasma aldosterone was observed, with maximum suppression at week 14 resulting in geometric mean changes of −49.5% (95% CI: −68.7, −18.5) and −52.1% (−70.7, −21.6) for vicadrostat 20 mg given with and without empagliflozin, respectively. From baseline to week 14, increases were observed in mean plasma corticosterone, 11-deoxycorticosterone, and 11-deoxycortisol. Plasma 11-deoxycorticosterone increased by 222.8% (95% CI: 103.2, 412.7) and 231.5% (95% CI: 106.4, 432.2) for vicadrostat 20 mg given with or without empagliflozin, respectively, and plasma 11-deoxycortisol increased by 112.5% (95% CI: 36.0, 231.9) and 121.0% (95% CI: 40.0, 249.0) for the same dose groups. No increase or decrease in plasma cortisol was observed across vicadrostat dose groups with or without empagliflozin. Aldosterone suppression was sustained to 4 weeks post-treatment, while precursor levels normalized within 1 week of treatment cessation.Vicadrostat, with or without background empagliflozin, selectively suppressed aldosterone over cortisol. These findings will be explored in a phase 3 trial program.